How the brain codes intimacy: The neurobiological substrates of romantic touch - Kreuder, Ann‐Kathrin; Scheele, Dirk; Wassermann, Lea; Wollseifer, Michael; Stoffel‐Wagner, Birgit; Lee, Mary R.; Hennig, Juergen; Maier, Wolfgang; Hurlemann, René (Human brain mapping, 2017)
Humans belong to a minority of mammalian species that exhibit monogamous pair‐bonds, thereby enabling biparental care of offspring. The high reward value of interpersonal closeness and touch in couples is a key proximate mechanism facilitating the maintenance of enduring romantic bonds. However, surprisingly, the neurobiological underpinnings mediating the unique experience of a romantic partner's touch remain unknown. In this randomized placebo (PLC)‐controlled, between‐group, pharmacofunctional magnetic resonance imaging (fMRI) study involving 192 healthy volunteers (96 heterosexual couples), we intranasally administered 24 IU of the hypothalamic peptide oxytocin (OXT) to either the man or the woman. Subsequently, we scanned the subjects while they assumed that they were being touched by their romantic partners or by an unfamiliar person of the opposite sex, although in reality an identical pattern of touch was always given by the same experimenter. Our results show that intranasal OXT compared to PLC selectively enhanced the subjective pleasantness of the partner's touch. Importantly, intranasal OXT selectively increased responses to partner touch in the nucleus accumbens (NAcc) and anterior cingulate cortex. Under OXT, NAcc activations to partner touch positively correlated with the subjects' evaluation of their relationship quality. Collectively, our results suggest that OXT may contribute to the maintenance of monogamous relationships in humans by concomitantly increasing the reward value of partner touch and diminishing the hedonic quality of stranger touch. Hum Brain Mapp 38:4525–4534, 2017. © 2017 Wiley Periodicals, Inc.